Avaliação das condições de saúde do trabalhador na operação de derriça do café - Pomárico, Giovanni (2011)
Coffee harvest is one of the most important stages of production. A well done harvest influence the quality of the drink. Manual harvesting is the best option when it is intended to obtain a differentiated coffee. However, in fields, employees are submitted to a lot of health risk conditions. In this context, the worker who is responsible for the harvest must be healthy, in order to avoid diseases which may affect both their personal and professional life. The objective of this study was to evaluate the manpower involved in coffee harvest, identifying risks and proposing interventions to minimize them. The experiment was conducted in coffee cultures on the Campus of Universidade Federal de Lavras – UFLA, Brazil. A group of 15 coffee pickers was accompanied, and the following parameters were analyzed: body mass index (BMI), waist-hip ratio (WHR), blood pressure, hand grip, static posture evaluation, frequencies of use of upper articulations and trunk. For the manual harvester, data on the sound pressure level and vibration of the worker's forearm were collected. Regarding BMI, a balance was observed, where 47% of the workers were eutrophic and 53% were overweight and obese. Curiously, 87% were not below the maximum limit of the waist-hip ratio, i.e. there was no strong correlation among these parameters. About 67% of the workers had normal blood pressure, 27% had mild hypertension and 6% had moderate hypertension. Regarding hand grip, only one employee did not present good results. It was also observed that about 87% of the workers presented scoliosis, which worries the elder workers. For the frequency of use of upper articulations and trunk, all workers were above the recommended by ILO. For the sound pressure level, the manual harvester showed an average value of 92.52 dB(A), which allows permanence without personal protective equipment (PPE) for 3 hours daily. For the vibration transmitted to the worker´s arms, the maximum limit is two hours.